Estrategias didácticas para emplear reglas de la ortografía de los estudiantes del séptimo año de educación básica de la Unidad Educativa “Narcisa de Jesús”, de La Parroquia Febres Cordero, cantón Babahoyo, Provincia de Los Ríos - Estrada Chafla, Elsa Paola (2019)
This document will work on the main concepts related to didactic strategies in online courses. Actions planned by the teacher with the objective that the student achieves the construction of learning and the scope of the objectives set. A didactic strategy is, in a strict sense, an organized, formalized and oriented procedure to obtain a clearly established goal. Its application in daily practice requires the improvement of procedures and techniques whose specific choice and design are the responsibility of the teacher. Learning strategies are a flexible and conscious guide to achieve the objectives, proposed in the learning process. As a guide you must have certain steps taking into account the nature of the strategy. In particular, learning strategies in Distance Education must take into account the characteristics of the adult.